2022
DOI: 10.2196/35425
|View full text |Cite
|
Sign up to set email alerts
|

Online Peer Support for People With Parkinson Disease: Narrative Synthesis Systematic Review

Abstract: Background Parkinson disease (PD) significantly impacts the lives of people with the diagnosis and their families. In addition to the physical symptoms, living with PD also has an emotional impact. This can result in withdrawal from social roles, increasing the risk for social isolation and loneliness. Peer support is a way to stay socially connected, share experiences, and learn new coping skills. Peer support can be provided both in person and on the internet. Some of the advantages of online pee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
3
15
0
Order By: Relevance
“…32 The use of peers has been advocated as a means to support selfefficacy 33 and peer-led self-management intervention have been promoted for their cost-effective potential. 9,11 Our findings that, with training, intervention fidelity was largely maintained across sites delivered by different peer facilitators is therefore promising. Involving careers was a central component of First Steps and improved self-management has been associated with informal support from 'carers'.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…32 The use of peers has been advocated as a means to support selfefficacy 33 and peer-led self-management intervention have been promoted for their cost-effective potential. 9,11 Our findings that, with training, intervention fidelity was largely maintained across sites delivered by different peer facilitators is therefore promising. Involving careers was a central component of First Steps and improved self-management has been associated with informal support from 'carers'.…”
Section: Discussionmentioning
confidence: 83%
“…7,8 Peer support has also been found to produce psycho-social benefits, through sharing experiences, feelings of empowerment and social connectedness, all of which can help people with Parkinson's (PwP) develop new coping skills. 9 Peer-led interventions, by their nature, benefit from the credibility of the lived experience 10 and have been promoted as a cost-effective therapeutic opportunity to support others experiencing similar life circumstances. 11 While being peer led has the potential to add value to self-management interventions few studies have investigated this approach in Parkinson's.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, this review may over represent positive aspects of online peer support, since people who are active on an online platform tend to be the ones who enjoy it, only one study reported on the negatives and potential challenges of online peer support for people with ALS ( 22 ), and we could not include views and experiences of those who are unable to use or stopped using online peer support. Finally, with the qualitative content analysis methodology the findings can still remain dependent on the researchers’ interpretation ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic database search was conducted in April 2020 and updated in June 2022. The search was part of a wider appraisal of the literature on different chronic neurodegenerative conditions ( 19 , 20 ). Six databases were searched: CINAHL, Cochrane Library, Embase Medline, PsycINFO, Scopus, and Web of Science.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation